Wings, sun, and stars the story of bird migration. - Kaufmann, John. (New York Morrow, 1969)
Presents and discusses the reasons for bird migration, the biological facts of bird flight, timing and direction of migrations, and theories on the accuracy of migratory bird navigation.
Bibliography: p. 153-154.
Keywords: Birds -- Migration -- Juvenile literature; Birds -- Migration